Inhibition of histone deacetylase 6 suppresses inflammatory responses and invasiveness of fibroblast-like-synoviocytes in inflammatory arthritis - Jin Kyun Park (Arthritis Research & Therapy, 2021)
Abstract Background To investigate the effects of inhibiting histone deacetylase (HDAC) 6 on inflammatory responses and tissue-destructive functions of fibroblast-like synoviocytes (FLS) in rheumatoid arthritis (RA). Methods FLS from RA patients were activated with interleukin (IL)-1β in the presence of increasing concentrations of M808, a novel specific HDAC6 inhibitor. Production of ILs, chemokines, and metalloproteinases (MMPs) was measured in ELISAs. Acetylation of tubulin and expression of ICAM-1 and VCAM-1 were assessed by Western blotting. Wound healing and adhesion assays were performed. Cytoskeletal organization was visualized by immunofluorescence. Finally, the impact of HDAC6 inhibition on the severity of arthritis and joint histology was examined in a murine model of adjuvant-induced arthritis (AIA). Results HDAC6 was selectively inhibited by M808. The HDAC6 inhibitor suppressed the production of MMP-1, MMP-3, IL-6, CCL2, CXCL8, and CXCL10 by RA-FLS in response to IL-1β. Increased acetylation of tubulin was associated with decreased migration of RA-FLS. Inhibiting HDAC6 induced cytoskeletal reorganization in RA-FLS by suppressing the formation of invadopodia following activation with IL-1β. In addition, M808 tended to decrease the expression of ICAM-1 and VCAM-1. In the AIA arthritis model, M808 improved the clinical arthritis score in a dose-dependent manner. Also, HDAC6 inhibition was associated with less severe synovial inflammation and joint destruction. Conclusion Inhibiting HDAC6 dampens the inflammatory and destructive activity of RA-FLS and reduces the severity of arthritis. Thus, targeting HDAC6 has therapeutic potential.